The Role of Public Relations In Disseminating Information In The City of Cirebon (Case Study: Trans Cirebon Integrated Bus System) - Filiah Nuralifah; Siti Khumayah; Farida Nurfalah (Interaction Communication Studies Journal, 2026)
This study aims to analyze the role of public relations in disseminating information about public transportation, using the Trans Cirebon Bus Rapid Transit (BRT) as a case study. The background of this study is based on the still-limited dissemination of information regarding BRT routes, schedules, and services, which has resulted in low public interest in using public transportation. This study employs a qualitative approach using the case study method. Data were collected through in-depth interviews, field observations, and a literature review, with informants selected using purposive sampling. The theoretical framework consists of Dozier and Broom’s Theory of the Role of Public Relations and Cutlip and Center’s Communication Planning Strategy. The results indicate that public relations plays a crucial role in disseminating information through four primary functions: as an expert prescriber, a communication facilitator, a problem-solving process facilitator, and a communication technician. However, the implementation of these roles has not been optimal, particularly regarding the equitable distribution of information to the public. In addition, obstacles were identified, including limited route coverage, limited access to bus stops, and a lack of effective communication strategies. The limited dissemination of information is one of the factors contributing to low public interest, which has led to the suspension of Trans Cirebon BRT operations. Therefore, a more integrated and effective communication strategy is needed to raise awareness and encourage the use of public transportation among the public.